STRENGTHENING CHARACTER EDUCATION IN ADIWIYATA SCHOOLS - Astuti, Tri; Handoyo, Eko; Rohsulina, Pranichayudha; Chin, Chee Keong (Universitas Muhammadiyah Purwokerto, 2023)
The young generation's low concern for the environment and rampant anti-social behavior were reasons for implementing character education, especially in Adiwiyata schools. Strengthening character education in schools was very important. This study aimed to analyze the strengthening of character education at Adiwiyata schools, especially at Keturen 01 State Elementary School Tegal. The research method was qualitative, a type of case study. The subjects were students of class 4 Keturen 01 State Elementary School Tegal. Researchers collected data through in-depth interviews, observation, and documentation; he tested the validity of the data using technique and source triangulation. Data analysis included collecting data, sorting data, categorizing the data, and concluding. Based on research results, strengthening character education at Adiwiyata schools was developed based on the environment. Character education was carried out by implementing the dimensions of the Pancasila student profile. Teachers became facilitators in character education in schools, while students were trained and accustomed to thinking and behaving following Pancasila values and caring for the environment. These activities were carried out through learning activities and habituation activities at school. Based on this, the conclusion was that strengthening character education in schools had been going well. Students and teachers could overcome the obstacles.